Proceso de ASC - ESTUDIO CONCEPTUAL DE LA GASIFICACION POR PLASMA PARA LA PRODUCCION DE SYNGAS (2023)
Gasification is a thermochemical process through which waste materials, such as biomass, are transformed into synthesis gas (SYNGAS) to produce fuel gas that can be used as an energy vector. Energy generation from biomass typically involves combustible agents like wood, coal, and refined petroleum products, which are used for their ability to convert mass into thermal energy, which can then be transformed into mechanical work and even electrical energy. Plasma, or ionized gas, has various properties depending on its nature and can be either cold or hot plasma. Hot plasma can reach extremely high temperatures, even higher than those in combustion processes, enabling the transformation of both organic and inorganic matter by reaching their melting points. Thus, plasma is a valuable tool for gasification processes, converting matter (organic and inorganic) into synthesis gas. Additionally, the implementation of gasification processes seeks to benefit the environment through solid waste treatment, production of low or zero carbon footprint fuels, and sustainable energy. Consequently, knowledge about the use of high-temperature plasmas for solid waste treatment is of great scientific interest to the materials research group, due to its significant environmental and social impact.